2016
DOI: 10.1016/j.soncn.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Exposure and Its Impact on Skin Cancer Risk

Abstract: Objectives To review research and evidence-based resources on skin cancer prevention and early detection and their importance for oncology nurses. Data Sources Journal articles, federal reports, cancer surveillance data, behavioral surveillance data. Conclusion Most cases of skin cancer are preventable. Survivors of many types of cancer are at increased risk of skin cancers. Implications for Nursing Practice Oncology nurses can play an important role in protecting their patients from future skin cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 87 publications
(85 reference statements)
0
115
0
17
Order By: Relevance
“…Banská Bystrica and Košice regions are also very close each other together with the mortality from C43-C44 (Melanoma and other malignant neoplasms of skin). It is appreciated that there are higher concentration of ultraviolet radiation or solar exposure which influence melanoma skin cancer (26)(27)(28). For complex explanation of these causalities, medical analyses would have to be conducted in Slovak regions.…”
Section: Discussionmentioning
confidence: 99%
“…Banská Bystrica and Košice regions are also very close each other together with the mortality from C43-C44 (Melanoma and other malignant neoplasms of skin). It is appreciated that there are higher concentration of ultraviolet radiation or solar exposure which influence melanoma skin cancer (26)(27)(28). For complex explanation of these causalities, medical analyses would have to be conducted in Slovak regions.…”
Section: Discussionmentioning
confidence: 99%
“…UVA exposure causes free radical production that leads to oxidative damage and DNA damage indirectly. UVB causes DNA damage leading to driver and bystander mutations as well as photo by‐products leading to cellular transformation and malignancy . Despite the harmful photocarcinogenic and immune suppressive effects of sunlight, UVB wavelengths of 290‐315 nm are also responsible for vitamin D synthesis to carry out its endocrine function.…”
Section: Skin Carcinogenesis and Vitamin Dmentioning
confidence: 99%
“…Several reports suggest that systemic sclerosis (SSc), which mostly affects lungs, breasts, and the hematological system, is also associated with the increased risk of malignancy (Zeineddine et al, 2016). Exposure to ultraviolet (UV) radiation is another factor responsible for skin cancer as it stimulates skin cell damage, and intense exposures may even result in cell death (Watson et al, 2016). Moreover, recent reports revealed that oral environment is also associated with cancer as it functions as the bodily entrance for food and air and is exposed to various foreign substances including bacteria and viruses (Kudo et al, 2016).…”
Section: Other Factorsmentioning
confidence: 99%